2021
DOI: 10.3389/fpsyg.2021.755347
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors That Influenced the Mental Health Status of Public Health Workers During the COVID-19 Epidemic Based on Bayesian Networks: A Cross-Sectional Study

Abstract: Background: Public health workers are essential to responding to the coronavirus disease 2019 (COVID-19) epidemic, but research on anxiety and stress among public health workers during the epidemic is limited. This study aimed to evaluate related factors affecting mental health among public health workers during the epidemic.Methods: Between February 19 and 25, 2020, an online, cross-sectional study was conducted among public health workers in a city in China. Mental health status was assessed using the Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Students rated the frequency of these symptoms over the past 2 weeks. The severity of anxiety was classified according to the score as minimal or none (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), and severe (≥15). The scale's internal consistency coefficient was 0.92, the test-retest reliability was 0.83, and the correlation R with the Beck anxiety inventory (BAI) and the symptom check list-90 (SCL-90) were 0.72 and 0.74, respectively (18, 19).…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Students rated the frequency of these symptoms over the past 2 weeks. The severity of anxiety was classified according to the score as minimal or none (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), and severe (≥15). The scale's internal consistency coefficient was 0.92, the test-retest reliability was 0.83, and the correlation R with the Beck anxiety inventory (BAI) and the symptom check list-90 (SCL-90) were 0.72 and 0.74, respectively (18, 19).…”
Section: Anxietymentioning
confidence: 99%
“…In fact, public health and preventive medicine students have been hit hard by the pandemic, but they did not seem to receive much attention. Studies have confirmed that during the severe phase of the epidemic, COVID-19 elicits a strong psychological response among public health workers (13). In China, although they rarely directly work with clinical patients, most of them are involved in epidemic prevention and control at primary health organizations, the Centers for Disease Control (CDC), and hospital administrations.…”
Section: Introductionmentioning
confidence: 98%
“…The COVID-19 pandemic has also posed an increased risk to people with mental health problems. These people have struggled to receive their current treatments during the pandemic, and their support systems and resources have decreased, which has led to an increase and worsening of symptoms in people with psychological problems [3].…”
mentioning
confidence: 99%